2008
DOI: 10.1186/1471-2261-8-11
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of vasoactive substances during exercise modulates platelet aggregation in hypertension and coronary artery disease

Abstract: Background: Acute vigorous exercise, associated with increased release of plasma catecholamines, transiently increases the risk of primary cardiac arrest. We tested the effect of acute submaximal exercise on vasoactive substances and their combined result on platelet function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 36 publications
(29 reference statements)
2
31
1
Order By: Relevance
“…The findings of our investigation are consistent with evidence in the literature linking sympathetic function with diverse systemic and multiorgan derangements, including hypertension [46], myocardial ischemia [47], congestive heart failure [48], cardiac tachyarrhythmias [49], sudden cardiac mortality [50], abnormal renal natriuresis [51], enhanced platelet aggregation [52] and impaired immune function [53]. Sympathetically mediated neurogenic cardiopulmonary complications have been related to adverse outcomes following SAH [54], and sympathetic activity has been connected to increased inflammation and enhanced thrombosis [7,8], the markers of which predict detrimental outcomes in patients with SAH [18,20].…”
Section: Discussionsupporting
confidence: 78%
“…The findings of our investigation are consistent with evidence in the literature linking sympathetic function with diverse systemic and multiorgan derangements, including hypertension [46], myocardial ischemia [47], congestive heart failure [48], cardiac tachyarrhythmias [49], sudden cardiac mortality [50], abnormal renal natriuresis [51], enhanced platelet aggregation [52] and impaired immune function [53]. Sympathetically mediated neurogenic cardiopulmonary complications have been related to adverse outcomes following SAH [54], and sympathetic activity has been connected to increased inflammation and enhanced thrombosis [7,8], the markers of which predict detrimental outcomes in patients with SAH [18,20].…”
Section: Discussionsupporting
confidence: 78%
“…The observation that AMPK, AMPK regulatory proteins, and eNOS are activated after a single bout of exercise suggests they may be a critical component of these signaling events. Second, aerobic-type exercise can cause a hypercoagulant state associated with increases in platelet count (33), plasma catecholamines, thromboxane A2, and endothelin-1 release (39). The activation of eNOS, and secondarily NO release from the endothelium, could represent a counterbalance that maintains hemostasis during such physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that fibrinogen follows a circadian rhythm similar to the blood pressure. 23 The importance of blood hemostasis and the role of physical activity and circadian rhythm inspired the present study to investigate the effect of acute training and circadian rhythm on the blood hemostasis in female athletes.…”
Section: The Effect Of Acute Training and Circadian Rhythm On Blood Hmentioning
confidence: 99%